Design studies on a high-power wide-band RF combiner for consolidation of the driver amplifier of the J-PARC RCS. Issue 1 (1st January 2023) - Okita, H; Tamura, F; Yamamoto, M; Nomura, M; Shimada, T; Yoshii, M; Ohmori, C; Sugiyama, Y; Hasegawa, K; Hara, K; Paoluzzi, M M
Abstract: A power upgrade of the existing 8-kW solid-state driver amplifier is required for the acceleration of high intensity proton beams on the J-PARC 3-GeV Rapid Cycling Synchrotron. The development of a 25-kW amplifier with gallium nitride (GaN) HEMTs, based on 6.4-kW modules is ongoing. The combiner is a key component to achieve such a high output power over the wide bandwidth required for multi-harmonic RF operation. This paper presents the preliminary design of the combiner. The circuit simulation setup and results, including the realistic magnetic core characteristics and frequency response of the cable, are reported.